Qualitative Analysis of Chlorine (Cl2) and Formalin Content In Raw White Rice Crackers Produced in Sambipondok Village, Sidayu, Gresik - Dwi Indriani, auliya; Dhini Anggraini, Susanti (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Crackers are a snack made from starch that is popular with the public. According to a field survey, raw white crackers produced by UMKM in Sambipondok Village, Sidayu District, Gresik have a whiter or lighter color compared to other similar raw crackers. This condition is thought to be due to the addition of additional ingredients that are not recommended. This study aims to analyze the presence of Chlorine (Cl2) and Formalin qualitatively in raw white crackers produced by UMKM in Sambipondok Village, Sidayu District, Gresik. The method used in this study is a qualitative research method involving several chemical reagents that are in accordance with predetermined characteristics. In the analysis of Chlorine (Cl2) content using 10% Potassium iodide (KI) and 1% Starch reagents, 5% silver nitrate (AgNO3) solution, Lead acetate Pb(CH3COO)2. While in the analysis of formalin content using a formalin test kit brand labstest reagent, Fehling A and B solutions, and 0.1N KMnO4. The results of the study showed that raw white crackers produced by MSMEs in Sambipondok Village, Sidayu District, Gresik, were positive for containing Chlorine (Cl2) and Formaldehyde.